2014
DOI: 10.1180/minmag.2014.078.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Ekplexite (Nb,Mo)S2·(Mg1−xAlx)(OH)2+x, kaskasite (Mo,Nb)S2·(Mg1−xAlx)(OH)2+x and manganokaskasite (Mo,Nb)S2·(Mn1−xAlx)(OH)2+x, three new valleriite-group mineral species from the Khibiny alkaline complex, Kola peninsula, Russia

Abstract: Three new valleriite-group minerals, ekplexite (Nb,Mo)S2·(Mg1−xAlx)(OH)2+x, kaskasite (Mo,Nb)S2·(Mg1−xAlx)(OH)2+x and manganokaskasite (Mo,Nb)S2·(Mn1−xAlx)(OH)2+x are found at Mt Kaskasnyunchorr, Khibiny alkaline complex, Kola Peninsula, Russia. They occur in fenite consisting of orthoclase−anorthoclase and nepheline with fluorophlogopite, corundum, pyrrhotite, pyrite, rutile, mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…The precursors spontaneously self-assemble into alternating quasi-atomic Cu-Fe-S sulfide and Mg hydroxide sheets in the hydrothermal process through a mechanism that still needs to be understood. The structure of valleriites formed by incommensurate 2D layers allows to vary widely, and to some extent independently, their composition and then properties, including replacement both of metals and chalcogenide atoms [30][31][32][33][34][42][43][44][45][46][47][48][49][50]. On the other hand, the counterparts affect each other via the electric charges and probably other factors; this makes possible to finely adjust the material characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precursors spontaneously self-assemble into alternating quasi-atomic Cu-Fe-S sulfide and Mg hydroxide sheets in the hydrothermal process through a mechanism that still needs to be understood. The structure of valleriites formed by incommensurate 2D layers allows to vary widely, and to some extent independently, their composition and then properties, including replacement both of metals and chalcogenide atoms [30][31][32][33][34][42][43][44][45][46][47][48][49][50]. On the other hand, the counterparts affect each other via the electric charges and probably other factors; this makes possible to finely adjust the material characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…35[Mg0.74Al0.26(OH)2]. Minerals of the valleriite group [31][32][33][34] with iron dominance in hydroxide layers (mineral ferrovalleriite) [31,32] or chromium instead of iron in hydroxide and sulfide sheets [33], or FeS layers in place of CuFeS2 (tochilinite) [24,27,35,36] were discovered too. Valleriite is known [20,24,25,30] to crystallize in a hexagonal lattice with the sulfide sublattice being rhombohedral (space group R3m with hexagonal axes a = 0.3792 nm and c = 0.341 nm) and the hydroxide one having hexagonal lattice (space group P3m1, a = 0.307 nm and c = 1.137 nm).…”
Section: Introductionmentioning
confidence: 99%
“…The flake-like nanoparticles composed of altering quasi-atomic Cu-Fe-S sulfide and Mg hydroxide sheets are manufactured in the environment-friendly hydrothermal process using common reagents. Such a chalcogenide-hydroxide incommensurate structures looks unusual and complex but there exist a number of natural [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and synthetic [43][44][45][46][47][48][49][50][51] layered materials, suggesting that those are quite stable and spontaneously assemble via a mechanism that needs to be understood. The composition and then morphology and properties of the materials can be engineered by varying the nature and concentrations of precursors, modifiers, dopants far beyond those used in this case study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hughes et al [30] have reported the composition of synthetic valleriites ranged from [CuFeS2]1.67[Mg0.70Al0.30(OH)2] to [Cu1.30Fe0.70S2]1.35[Mg0.74Al0.26(OH)2]. Minerals of the valleriite group [31][32][33][34] can have prevalent iron in hydroxide layers (ferrovalleriite), [31,32] or chromium instead of iron in hydroxide and sulfide sheets. [33] These findings imply that such synthetic systems should be stable and their chemical composition could be widely varied and adjusted on demand.…”
Section: Introductionmentioning
confidence: 99%
“…, содержащие до 10 мас.% примесного вольфрама, который замещает молибден и ниобий в сульфидном модуле (Pekov et al, 2014). И.В.…”
Section: Introductionunclassified